Laser-induced transient strengthening of coupling in L10-FePt/FeNi exchange-spring film. (18th March 2015) - Chen, Zhifeng; Li, Shufa; Lai, Tianshu
Abstract: Laser-induced evolution of the coupling state in a perpendicular exchange-spring L 10 -FePt/FeNi bilayer film is studied via time-delayed magneto-optical polar Kerr loops. A transient strengthening process of the coupling is found to occur simultaneously with significant reduction of the hard-phase coercivity at 50 ps after the ultrafast demagnetization. Analysis of the time-dependent magnetization components and the micromagnetic calculation demonstrate that this delayed coupling-strengthening phenomenon originates from the opposite laser-modulation effects respectively on the hard and soft magnetic phases, in which the laser-induced transient reduction of the magnetic anisotropy in FePt phase plays the most important role.